Akuntansi Pesantren Sesuai SAK ETAP dan PSAK 45 dalam Penyusunan Laporan Keuangan Pesantren - Sulistiani, Dwi (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This study aims to determine the process of preparing financial statements in terms of recognition, measurement, recording, disclosure, and presentation. This descriptive qualitative study uses primary data with the method of observation, interviews, and Focus Group Discussion, while the secondary data uses the method of literature and documentation. The results show that the Islamic boarding school had not prepared its financial statements in accordance with SAK ETAP, in terms of recognition, measurement, recording, and disclosure. This boarding school uses a single entry system in preparing financial statements and did not present its financial reports in accordance with PSAK 45. Sabilirrosyad just make one report that is cash flow. That is due to the lack of human resources who understand related to accounting. BI and IAI can prepare the socialization and workshop for Islamic boarding schools in order to make the accounting manual book for Islamic boarding schools effectively.